How can the vortex filament equation $$\partial_t \chi = \partial_s \chi \wedge \partial_{ss} \chi,$$ where $\chi(t,s)$ is a curve in $\mathbb R^3$, be derived from the Euler equation $$\partial_t \omega + v\cdot \nabla \omega = \omega \cdot \nabla v, \quad \operatorname{div} v = 0,$$ where $v:\mathbb R \times \mathbb R^3 \to \mathbb R^3$, and $\omega = \operatorname{curl}(v):\mathbb R \times \mathbb R^3 \to \mathbb R^3.$

I've asked a more general question at Survey on the vortex filament equation.

  • $\begingroup$ you can find a detailed derivation in arxiv.org/abs/1603.00227 . $\endgroup$ May 15 '19 at 20:11
  • $\begingroup$ @CarloBeenakker Thank you. That's very helpful. $\endgroup$
    – Kei
    May 15 '19 at 21:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.